PERTANGGUNGJAWABAN PIDANA DALAM PENGALIHAN SAHAM TANPA MELALUI RAPAT UMUM PEMEGANG SAHAM DALAM PRESFEKTIF UNDANG-UNDANG PERSEROAN TERBATAS DAN KUHP INDONESIA - MIRZA AMELIA; IDRIS SARDI; AWALUDIN AWALUDIN (Universitas Mahasaraswati K. Mataram, 2024)
Share transfer is an activity that is legalized by the government trough legislation, in addition to being regulated in Law No 40 of 2007 concerning Limited Liability Companies, it is also regulated in the Indonesia Civil Code Article 1457 of civil Code. The Legal Issues raised in this study are related to how criminal Liability is in the transfer of shares without going through a GMS as viewed from the perspective of Law No 40 of 2007 concerning Limited Liability Companies and Law No 1 of 1946 Concerning The Criminal Code and Subsequent issues related to what are the obstacles when Criminal acts and Criminal Liability in the transfer of shares that do not go through a GMS are reviewed from Law No 40 of 2007 Concerning Limited Liability Companies and Law No 1 of 1946 Concerning The Criminal Code That whwn There is a Criminal case related to the transfer of shares, how is the criminal Liability and what are the obstcles in handing it? That criminal Liability for the transfer of share has not been regulated regarding sanctions, botg administrative and criminal sanctions because they still refer to the Criminal Code and this is and obstacle in the Criminal process if it occurs in a limited liability Company, criminal liability in alimited liability company is in article 1 of Law No 1 of 2023 concerning the Criminal Code. In this study, the method used is the normative legal method with several approaches, namely the statute approach and the analytical approach and secondary legal material.